Entrepreneurship for everyone : a student textbook - Mellor, Robert B.; Mellor, Robert (Sage Publications, 2009)
Brings to the non-specialist not only the crucial issues of entrepreneurship, but also bridges the gap between business knowledge and expert knowledge from other disciplines.